1994
DOI: 10.2307/1131379
|View full text |Cite
|
Sign up to set email alerts
|

Children's Relationships with Peers: Differential Associations with Aspects of the Teacher-Child Relationship

Abstract: Associations between children's social competence with peers and differential aspects of their teacher-child relationships were examined in a longitudinal sample of 48 4-year-old children enrolled in child care as infants. Toddler security with teacher was negatively associated with hostile aggression and positively with complex peer play and gregarious behaviors. Prosocial behaviors and withdrawing behaviors were associated with preschool security with teacher. Dependence on teachers as a preschooler was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
2
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(117 citation statements)
references
References 0 publications
4
102
2
8
Order By: Relevance
“…While a large body of research shows positive developmental outcomes of mother-infant security of attachment (Weinfield et al, 1999), fewer studies have explored the longer-term consequences and nature of attachment security in infant daycare. Longitudinal data, however, has indicated that infants who are securely attached to an early childhood teacher are likely to become more empathetic, independent, and achievement-oriented, and to engage in more complex and cooperative peer play and more dramatic play than their insecurely attached peers (Oppenheim et al, 1988;Howes et al, 1994;Howes, 1997;Cassibba et al, 2000). Such findings do suggest that infants' attachment security with their early childhood teachers has long-term implications for their play and socio-emotional development.…”
Section: Relationship Quality Through the Lens Of Attachment Theorymentioning
confidence: 99%
“…While a large body of research shows positive developmental outcomes of mother-infant security of attachment (Weinfield et al, 1999), fewer studies have explored the longer-term consequences and nature of attachment security in infant daycare. Longitudinal data, however, has indicated that infants who are securely attached to an early childhood teacher are likely to become more empathetic, independent, and achievement-oriented, and to engage in more complex and cooperative peer play and more dramatic play than their insecurely attached peers (Oppenheim et al, 1988;Howes et al, 1994;Howes, 1997;Cassibba et al, 2000). Such findings do suggest that infants' attachment security with their early childhood teachers has long-term implications for their play and socio-emotional development.…”
Section: Relationship Quality Through the Lens Of Attachment Theorymentioning
confidence: 99%
“…For instance, better teacher–student relationships have been associated with fewer anti-social behaviors (Lang et al 2013; Silver et al 2005; Tiet et al 2010) and more prosocial behavior in childhood (Howes et al 1994; Roorda et al 2014; Wentzel 1998). Some studies have found age-limited effects, for example, Howes et al (1994) showed that students’ relationships with their teachers at age one and two were not related to later prosocial behavior but their relationship with their teacher in preschool, at age three, was. However, the flip side of the greater ecological validity of observational data is that it creates challenges with respect to accounting for alternative explanations for an apparent causal effect of relationship quality on behavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This transition is easy for some children; but it can be quite challenging for others since it requires them to adapt to new environments and develop new social relationships (Gagnon et al, 2014). Children with high social competence are good at social interactions (Rose-Krasnor, 1997) and these children exhibit effective problem solving, emotion regulation and communication skills (Hart, Olsen, Robinson, & Mandleco, 1997), sensitivity and empathy towards peers, complex play skills, friendship development and social problem solving skills (Howes, Hamilton, & Matheson, 1994). On the other hand, the lack of social competence is considered as a risk factor for both current and long-term adaptation problems and difficulties in interpersonal relationships (Pearson & Rao, 2003).…”
Section: Introductionmentioning
confidence: 99%